Criminal Liability for Forgery of Meningitis Vaccine Quarantine Documents for Umrah-Hajj Travelers from the Perspective of the Criminal Code and Health Law - Sembiring, J. (IJBLE Scientific Publications Community Inc., 2025)
The Hajj and Umrah pilgrimages are spiritual obligations for Muslims that require not only physical and financial readiness, but also compliance with legal regulations, including international health aspects. The COVID-19 pandemic has led to the implementation of strict regulations, including vaccination requirements and quarantine documents for pilgrims. The issuance of health quarantine documents is not immune to criminal acts involving the forgery of such documents to facilitate the departure process, whether physically or electronically. The forgery of quarantine documents has serious implications under Indonesian criminal law, particularly regarding public health protection. This paper aims to analyze the forms of criminal liability for perpetrators of quarantine document forgery in the context of Hajj and Umrah travel, as well as to examine future policies on criminal sanctions. The research method used is normative legal analysis with a legislative and conceptual approach, analyzed through a literature review of primary, secondary, and tertiary legal sources. The research findings indicate that the forgery of quarantine documents constitutes a criminal offense regulated under Article 263 of the Criminal Code, Article 391 of the New Criminal Code, and Article 444 of the Health Law. Criminal punishment for perpetrators is not only repressive but also serves a preventive function to safeguard the collective safety of the international community. Criminal liability may be imposed on the principal perpetrator and accomplices, with an emphasis on the element of intent as a violation of the fundamental values of human rights in the field of health